(3dhYI GdTGcj hOeYI GdHGcjs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3dGHO ef Tchi Edi Pj eQhAI jhGSjc Ch jSjdc Ch jJhLY s
(3BNQgG (B:s
(3eHJhQ hBNQ GdehLhO ajgG(B: (3heG MRfc hCfG JMJ ChGeQc hfhGgjc, abdJ dg(B: (3hGddg eG CHcGfj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B26 - (3U(B34s
(3fSNI KGfjIs
(3JJab aj ChdgG eY Chd GdfSNI GdChdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B174 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1570s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs